Innate Variability in Physiological and Omics Aspects of the Beta Thalassemia Trait-Specific Donor Variation Effects - Anastasiadi, Alkmini T.; Tzounakas, Vassilis L.; Dzieciatkowska, Monika; Arvaniti, Vasiliki-Zoi; Papageorgiou, Effie G.; Papassideri, Issidora S.; Stamoulis, Konstantinos; D’Alessandro, Angelo; Kriebardis, Anastasios G.; Antonelou, Marianna H. (Frontiers in Physiology, 2022)
The broad spectrum of beta-thalassemia (βThal) mutations may result in mild reduction (β++), severe reduction (β+) or complete absence (β0) of beta-globin synthesis. βThal heterozygotes eligible for blood donation are “good storers” in terms of red blood cell (RBC) fragility, proteostasis and redox parameters of storage lesion. However, it has not been examined if heterogeneity in genetic backgrounds among βThal-trait donors affects their RBC storability profile. For this purpose, a paired analysis of physiological and omics parameters was performed in freshly drawn blood and CPD/SAGM-stored RBCs donated by eligible volunteers of β++ (N=4), β+ (N=9) and β0 (N=2) mutation-based phenotypes. Compared to β+, β++ RBCs were characterized by significantly lower RDW and HbA2 but higher hematocrit, MCV and NADPH levels in vivo. Moreover, they had lower levels of reactive oxygen species, markers of oxidative stress and dihydrothymine, already from baseline. Interestingly, their lower myosin and arginase membrane levels were accompanied by increased cellular fragility and arginine values. Proteostasis activity markers (proteasomal activity and/or chaperoning-protein binding on the membrane) seem to be also diminished in β++ cells as opposed to the other two phenotypic groups. Overall, it seems that the second level of genetic variability among the group of βThal trait donors is reflected not only in the physiological features of RBCs in vivo, but almost equally in their storability profiles. Mutations that only slightly affect the globin chain equilibrium direct RBCs towards phenotypes closer to the average control, at least in terms of the fragility indices and the proteostatic dynamics.